2009
DOI: 10.2166/wst.2009.622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alternative electron donors for denitrifying moving bed biofilm reactors (MBBRs)

Abstract: The effectiveness of four different electron donors, specifically methanol, ethanol, glycerol, and sulfide (added as Na(2)S), were evaluated in post-denitrifying bench-scale moving bed biofilm reactors (MBBRs). With the requirement for more wastewater treatment plants to reach effluent total nitrogen levels approaching 3 mg/L, alternative electron donors could promote more rapid MBBR startup/acclimation times and increased cold weather denitrification rates compared to methanol, which has been most commonly us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…Bill, 2009, Uprety, 2012 showed similar responses to what was observed at the 26 th Ward WWTP. The key behavior to be accounted for by the model is summarized below:…”
Section: Modeling Approachsupporting
confidence: 63%
“…Bill, 2009, Uprety, 2012 showed similar responses to what was observed at the 26 th Ward WWTP. The key behavior to be accounted for by the model is summarized below:…”
Section: Modeling Approachsupporting
confidence: 63%
“…Denitrification. Denitrification in an MBBR has been studied extensively by Aspegren et al (1998), Bill et al (2009), Mases et al (2010), Rusten et al (1996), and Rusten, Hem, and Ødegaard (1995b). The rate of denitrification in an MBBR is influenced by the biofilm area, type of external carbon source, bulk-liquid carbon-to-nitrogen ratio (C:N), wastewater temperature, bulkliquid dissolved oxygen concentration, and bulk-liquid macronutrient concentrations.…”
Section: Process Flow Sheets and Bioreactor Configurationsmentioning
confidence: 99%
“…Bill et al [71] did research to evaluate the effectiveness of four different electron donors, specifically methanol, ethanol, glycerol and sulfide in post-denitrifying bench-scale MBBRs. Maximum denitrificaion rate measurements from profile testing suggested that sulfide, ethanol and glycerol substrates exhibited rates greater than methanol.…”
Section: Moving Medium Biofilm Reactorsmentioning
confidence: 99%